The TRIPLE Melting Probe - an Electro-Thermal Drill with a Forefield Reconnaissance System to Access Subglacial Lakes and Oceans - Heinen, Dirk; Audehm, Jan; Becker, Fabian; Böck, Georg; Espe, Clemens; Feldmann, Marco; Francke, Gero; Friend, Pia; Haberberger, Niklas; Helbin, Klaus; Nghe, Chi Thanh; Stelzig, Michael; et al. (OCEANS 2021: San Diego – Porto, 2021)
Recent measurements suggest the Jovian satellite Europa as one of the most promising places to host extraterrestrial life. Its global ocean is well hidden by a kilometer-thick layer of ice. Many currently discussed space missions therefore aim to explore Europa.The TRIPLE projects, initiated by the DLR Space Administration, comprise the development of Technologies for Rapid Ice Penetration and subglacial Lake Exploration, and consists of three components: (i) a melting probe, that travels through the ice and carries (ii) a small autonomous underwater vehicle (nanoAUV) that explores the ocean and takes samples to be delivered to (iii) an astrobiological laboratory. The full system should be demonstrated in a terrestrial analog mission in Antarctica in about five years. For a successful demonstration we need a retrievable melting probe capable of penetrating several kilometres of ice while avoiding obstacles and navigating around them. It has to be able to stop and dwell at the icewater boundary, before returning back to the surface. Within the projects TRIPLE-IceCraft and TRIPLE-FRS key technologies of such a melting probe are developed.The TRIPLE-IceCraft melting probe is designed as a modular system transporting standardised payloads through ice sheets of several hundred meters of thickness and penetrating into a subglacial water reservoir. Possible payloads are e.g. the nanoAUV or in-situ analysis devices for water samples such as a fluorescence spectrometer. The melting probe will be demonstrated at the Ekstrom shelf ice in Antarctica at the end of the project early 2023.The forefield reconnaissance system developed within TRIPLE-FRS combines radar and sonar techniques to benefit from both sensor principles inside ice. The radar antennas together with a specialized pulse amplifier as well as a piezoelectric acoustic transducer will be integrated into the melting head. To account for the respective propagation speed of electromagnetic waves, an in-situ permittivit...<br